Mechanisms and indicators for assessing the impact of biofuel feedstock production on ecosystem services. (July 2018) - Gasparatos, Alexandros; Romeu-Dalmau, Carla; von Maltitz, Graham P.; Johnson, Francis X.; Shackleton, Charlie; Jarzebski, Marcin P.; Jumbe, Charles; Ochieng, Caroline; Mudombi, Shakespear; Nyambane, Anne; Willis, Katherine J.
Abstract: Biofuel feedstock production can be a significant driver of landscape modification, ecosystem change and biodiversity loss. There is growing body of literature that shows how biofuel landscapes provide various ecosystem services (e.g., feedstock for fuel, carbon sequestration) and compromise other ecosystem services (e.g., food, freshwater services). These effects are context-specific and depend largely on prior land use conditions and feedstock production practices. Changes in the flow of ecosystem services due to the conversion of natural and agricultural areas can have ripple effects on human wellbeing. Despite some recent attempts to apply to biofuel settings concepts and methods rooted in the ecosystem services literature, this is the exception rather than the rule within both the biofuel and the ecosystem services research communities. This paper synthesizes the current knowledge about the impact of biofuels on ecosystem services. It focuses especially on the feedstock production phase and outlines the main mechanisms through which landscape conversion affects the provisions of ecosystem services. It proposes conceptually coherent indicators to reflect these mechanisms and offers a critical discussion of key issues at the interface of biofuels and ecosystem services. Highlights: Feedstock production is associated with all common drivers of ecosystem change. Feedstock production has positive or negative impacts to several ecosystem services. Conceptually coherent indicators were developed for the different impact mechanisms. Ecosystem services perspective is incompatible with key biofuel impacts and assessment tools.